Description of the second- and third instar larvae of Platynectes (s. str.) decemnotatus (Aubé, 1838) (Coleoptera: Dytiscidae: Agabinae: Platynectini) - Benetti, Cesar J.; Michat, Mariano C.; Alarie, Yves; Hamada, Neusa (Zootaxa, 2019)
The second- and third instar larvae of Platynectes (s. str.) decemnotatus (Aubé, 1838) are described and illustrated in detail for the first time, with special emphasis on morphometry and chaetotaxy. Larvae of P. decemnotatus can be distinguished from most other Agabinae by having secondary setae on the urogomphus and share with the other known species described in detail the presence of a ventroapical spinula on antennomere 3 and the absence of an occipital suture, natatory dorsal setae on tibia and tarsus and natatory setae on urogomphus. Platynectes decemnotatus larvae differ from larvae of Agabus Leach, 1817, Hydrotrupes Sharp, 1882 (currently in Hydrotrupini), Ilybiosoma Crotch, 1873, Ilybius Erichson, 1832 and the previously described Platynectes species in having a one-segmented urogomphus, a character previously observed only in larvae of Agabinus Crotch, 1873. The second- and third instar larvae of P. decemnotatus differ from those of P. (Agametrus) curtulus (Régimbart, 1899) in having the apical lateroventral process of antennomere 3 protruding (not protruding in P. curtulus). The third-instar larva of P. decemnotatus can also be distinguished from that of P. (Gueorguievtes) decempunctatus (Fabricius, 1775) by the absence of secondary dorsal setae on the tibia.